2023
DOI: 10.3390/agronomy13020295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bioactive Composition in Oryza sativa L. cv. KDML105 Bran Extract on Gene Expression Related to Hair Cycle in Human Hair Follicle Dermal Papilla Cells

Abstract: The aim of this study is to identify the effects of KDML105 bran extract on gene expression involving the hair cycle in HFDPCs and investigate its bioactive constituents, antioxidant, and anti-inflammatory activities. The content of tocopherols, γ-oryzanol, phytic acid, and phenolic compounds was quantified by liquid chromatography. Free fatty acids were determined using gas chromatography. Antioxidant capacities were estimated by DPPH, ABTS, and metal chelating assay. The nitric oxide (NO) production was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…The prevalence of androgenetic alopecia (AGA) is expected to rise in elderly people [8,9]. Generally, the main stages of hair follicle regeneration consist of the stages of growth (anagen), regression (catagen), resting (telogen), and shedding (exogen), which are affected by several factors [10]. In fact, the most common factor in AGA is the androgen hormone.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of androgenetic alopecia (AGA) is expected to rise in elderly people [8,9]. Generally, the main stages of hair follicle regeneration consist of the stages of growth (anagen), regression (catagen), resting (telogen), and shedding (exogen), which are affected by several factors [10]. In fact, the most common factor in AGA is the androgen hormone.…”
Section: Introductionmentioning
confidence: 99%
“…Keratinocyte and fibroblast cells are predominantly induced to proliferate and migrate to the unhealed edges of wounds [10]. Previous studies have reported that the activation of Wnt/β-catenin and sonic hedgehog signaling pathways can result not only in the migration of resident skin cells, mainly keratinocytes and dermal fibroblasts [14,15], but also in the proliferation of hair shafts [16][17][18]. Afterwards, blood vessels are developed in the wound bed and supply the necessary oxygen and nutrients [10].…”
Section: Introductionmentioning
confidence: 99%